YY1 represses beta-casein gene expression by preventing the formation of a lactation-associated complex. - Raught, B (1994)
Site-specific mutagenesis of the highly conserved milk box (-140 to -110) region suggested that beta-casein expression is regulated by a hormone-mediated relief of repression (M. Schmitt-Ney, W. Doppler, R. K. Ball, and B. Groner, Mol. Cell. Biol. 11:3745-3755, 1991). However, when this sequence was placed upstream of a heterologous thymidine kinase promoter, it activated reporter gene expression. This apparent paradox was resolved when the trans-acting factor YY1, capable of acting as both a positive and negative regulator, was shown to interact with the milk box region, using bacterially expressed YY1 and specific oligonucleotide and antibody competition experiments. Second, it was demonstrated that extracts prepared from several cell types contained a protein(s) interacting with the mammary gland-specific factor (MGF) binding site, previously shown to be required for beta-casein promoter activity (Schmitt-Ney et al., Mol. Cell. Biol. 11:3745-3755, 1991). Sequence analysis of this site revealed similarity to the gamma interferon-activated sequence, suggesting that MGF may be related to the stat91 signaling protein. Finally, using an oligonucleotide encompassing both the YY1 and MGF sites, we detected a slow-mobility complex only in extracts from mammary glands at late pregnancy and lactation (lactation-associated complex [LAC]). Site-specific mutation of the YY1 binding site led to an enhancement in LAC DNA binding activity, while mutation of the MGF site decreased detectable LAC. These results support a model in which lactogenic stimuli lead to a decrease in YY1 binding, and subsequent increased formation of LAC at a nearby binding site, to stimulate beta-casein transcription.